Draft genome sequence of Marinomonas fungiae strain AN44T (JCM 18476T), isolated from the coral Fungia echinata from the Andaman Sea - Kumari, Prabla; Badhai, Jhasketan; Das, Subrata K. (Genome Announcements, 2018)
Marinomonas fungiae strain AN44Twas isolated from mucus of the coralFungia echinataOptimum growth occurs at 3 to 5% NaCl. The draft genome is 4.2 Mb, with 3,776 protein-coding genes. It harbors genes for the degradation of aromatic compounds, such as quinate, ferulate,p-coumarate, protocatechuate, andp-hydroxyphenylacetate.

Morphological and molecular characterization of Penicillium rubens sp.nov isolated from poultry feed - Sawant, Amol M.; Vankudoth, Ramu; Navale, Vishwambar; Kumavat, Rajkamal; Kumari, Prabla; Santhakumari, B.; Vamkudoth, Koteswara Rao (Indian Phytopathology, 2019)
Fungi are the second largest group of eukaryotic organisms, estimates ranging from 2.2 to 3.8 million and 120,000 currently accepted species. Unfortunately, identification of Penicillium species is an overwhelming task even for taxonomic experts. In the current study, we isolated identified and morphologically characterized Penicillium rubens strain NCIM-1397. Molecular characterization of P. rubens by multilocus sequence analysis (MLSA) of internal transcribed spacer (ITS) region, β-tubulin (BenA), calmodulin (CaM), NL (D1/D2 region) and LR (large subunit region) gene. Conversely, BenA gene differentiated P. rubens from P. chrysogenum. Moreover, Vitek MS, Matrix-assisted laser desorption ionization–time of flight mass spectrometer (MALDI-TOF–MS) failed to discriminate to strain level. Metabolic profiling of P. rubens enable to produce roquefortine C, chrysogine, meleagrine, sorbicillin and non-producers for industrially important metabolite, penicillin determined by LC–MS. Even, In addition, even molecular detection of penicillin biosynthetic pathway genes, PcbC, PenDE and Phl were negative by PCR. Nevertheless, P. rubens showed 90–100% toxicity/pathogenicity on seed germination of sorghum (Sorghum bicolor) and no further development of coleoptiles, radicle and leaf length observed. Also, it showed non-toxic to animal cell determined on Human foreskin fibroblast (HFF) cell line by In-Vitro.

Characterization of multidrug resistance in Vibriospecies isolated from marine invertebrates from Andaman Sea - Kumari, Prabla; Poddar, Abhijit; Das, Subrata K. (3 Biotech, 2020)
This study describes the abundance of multidrug-resistantVibriosassociated with marine invertebrate hosts from the Andaman Sea, India. Thirty-eightVibriostrains were isolated from surface mucus layers of coralPorites,Goniastrea, Pocillopora, Fungia, and eggs of spiny lobster (Panulirus penicillatus). Phenotypically, the majority of strains exhibited growth at a wide range of temperatures, salt tolerance, and diverse nutritional requirements. All the strains had more than 97% 16S rRNA sequence similarity with type species of the genusVibriowhereVibrio fortis, andVibrio alginolyticuswere predominant. Multilocus Sequence Analysis (MLSA) using eight housekeeping genes namelyftsZ,gapA,gyrB,mreB,pyrH,recA,rpoA,andtopAdistributed the strains into 6 reported clades i.e.,Harveyi, Ponticus, Nereis, Orientalis, Splendidus,andMediterraneiwhere nearly half of the total strains represented the cladeHarveyi, followed by the cladeSplendidus.Likewise, the PFGE profile indicated genomic heterogeneity among the strains resulting in their distribution in five major clusters. Resistance to different antimicrobials was tested following the disc diffusion method where all strains were found susceptible to chloramphenicol (30 mu g) and resistant to streptomycin (10 mu g), vancomycin (30 mu g), sulfamethoxazole-trimethoprim (25 mu g). Moreover, the resistant phenotype to other antimicrobials confirmed the abundance of multidrug resistance strains in this marine environment.
Keywords: Drug-resistant; Genetic diversity; marine invertebrate; Multilocus sequence analysis; Vibrio